2019
DOI: 10.3390/ijms20040960
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical and Interfacial Properties of Bio-Composites Based on Poly(Lactic Acid) with Natural Cellulose Fibers

Abstract: The circular economy policy and the interest for sustainable material are inducing a constant expansion of the bio-composites market. The opportunity of using natural fibers in bio-based and biodegradable polymeric matrices, derived from industrial and/or agricultural waste, represents a stimulating challenge in the replacement of traditional composites based on fossil sources. The coupling of bioplastics with natural fibers in order to lower costs and promote degradability is one of the primary objectives of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 47 publications
3
59
0
Order By: Relevance
“…Micro-cavitation and micro-debonding can occur, introducing cracks of significant sizes [ 44 ]. Calcium carbonate can give rise to an improvement in fracture toughness when the mechanism of debonding is triggered in the presence of brittle matrices [ 45 ]. Charpy impact strength values test , performed on the PLA/PBAT biocomposites with mussel shell powder (see the last column of Table 3 ) revealed that the energy absorbed was approximately half with respect to that of the ductile matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Micro-cavitation and micro-debonding can occur, introducing cracks of significant sizes [ 44 ]. Calcium carbonate can give rise to an improvement in fracture toughness when the mechanism of debonding is triggered in the presence of brittle matrices [ 45 ]. Charpy impact strength values test , performed on the PLA/PBAT biocomposites with mussel shell powder (see the last column of Table 3 ) revealed that the energy absorbed was approximately half with respect to that of the ductile matrix.…”
Section: Resultsmentioning
confidence: 99%
“…This is a commercial grade containing about 4% of D-lactic acid units that lower the melting point and the crystallization tendency, improving the processing ability. This PLA, according to the producer's data sheet has a density of 1.24 g/cm 3 3 and a molecular weight of 402.5 g/mol.…”
Section: Methodsmentioning
confidence: 99%
“…This problem has encouraged research and industrial interest on biobased and biodegradable polymers that could overcome sustainability issues and environmental challenges posed by the production and disposal of oil-derived plastics [1,2]. In packaging and agriculture applications, the use of bio-based biodegradable polymers is a strong advantage both for environment and customers [3]. However, it is expected that the demand for these biopolymers will increase and, over the coming few decades, bioplastic materials can complement and gradually substitute the oil-based plastics in different sectors [2,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of polysaccharidic fibers in biopolyesters, such as PLA-based blends, as reinforcing agent [ 149 ] is a well-known alternative for producing micro- or nano-biocomposites [ 151 , 152 ]. In general, the mechanical properties of a biocomposite result from the matrix and fiber properties as well as the adhesion between the fibers and the matrix [ 153 , 154 ]. The tensile strength highly depends on the adhesion between the fibers and the matrix, whereas the tensile modulus is highly influenced by the distribution and orientation of the fibers and their length-to-width ratio (aspect ratio).…”
Section: Materials Modification Treatment and Processingmentioning
confidence: 99%